2014
DOI: 10.1080/01419870.2014.887744
|View full text |Cite
|
Sign up to set email alerts
|

Freedom of religion, women's agency and banning the face veil: the role of feminist beliefs in shaping women's opinion

Abstract: Several countries have imposed bans on the wearing of face veils, a controversial option considered in Bill 94 by the province of Quebec in 2010. This paper examines non-Muslim women's support for the acceptability of the niqab in public spaces. Analysing the 2010 Quebec Women's Political Participation Survey, we find that key feminist arguments -that wearing the niqab is a woman's free choice, a matter of freedom of religion and a visible symbol of women's oppression -are important drivers of opinion. Their r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 26 publications
1
26
0
1
Order By: Relevance
“…Other studies have also explored attitudes toward religious accommodation (Wright et al, 2017; Dufresne et al, 2018). However, none have systematically explored the impact of holding liberal values, although O'Neill et al (2015) show the determinant role played by feminist arguments. Moreover, in a study of the sources of support for the Charter of Quebec Values (Bilodeau et al, 2018), we found that supporters of both the Charter and the removal of the crucifix from the National Assembly of Quebec were more liberal than those who opposed the Charter.…”
Section: Notesmentioning
confidence: 99%
“…Other studies have also explored attitudes toward religious accommodation (Wright et al, 2017; Dufresne et al, 2018). However, none have systematically explored the impact of holding liberal values, although O'Neill et al (2015) show the determinant role played by feminist arguments. Moreover, in a study of the sources of support for the Charter of Quebec Values (Bilodeau et al, 2018), we found that supporters of both the Charter and the removal of the crucifix from the National Assembly of Quebec were more liberal than those who opposed the Charter.…”
Section: Notesmentioning
confidence: 99%
“…Although not expressly stated, it was “generally understood to be aimed at Muslim women who wear the niqab (full-face veil), and would essentially prohibit niqabi women from accessing public services” (Sharify-Funck, 2011: 136). As with Bill 60, feminists were not of one voice on Bill 94 (Conway, 2012; O'Neill et al, 2015: 1887); however, a closer examination of the former provides a more comprehensive illustration of the challenges under scrutiny in this paper.…”
Section: Part Iii: Bill 60 Controversies and Contentionsmentioning
confidence: 97%
“…These moves are not limited to the PQ's Bill 60 (or Charter of Values), introduced November 7, 2013. Consider here the Charter's unsuccessful precursor, the Liberal government's Bill 94 (Conway, 2012; Golnaraghi and Mills, 2013; Narain, 2014; O'Neill et al, 2015), or the Liberals' current attempt to foster official secularism in the public domain, Bill 62. However, given the circumstances elucidated below, the focus here is on Bill 60.…”
mentioning
confidence: 99%
“…While religious value systems have been shown to influence political choices (Olson, Cadge, & Harrison, 2006), attitude towards public policy (Baumgartner, Francia, & Morris, 2008), world views (Kelley & DeGraaf, 1997) and even cultural lifestyle choices such as dressing (O'Neill, Gidengil, Cote, & Young, 2015) in various parts of the world, African countries stand out in terms of the endorsement of the importance of religion and attendance of religious services, and the number of religious organizations (Gilani, Shahid, & Zuettel, 2012; Inglehart & Welzel, 2005; Kelley & DeGraaf, 1997). …”
Section: Introductionmentioning
confidence: 99%